Corporate sustainability of SHC in the construction industry - Evaluation and implications - Pham, Dan Kha (H. : ĐHQGHN, 2020)
The research aimed to identify the comparative business performance of SHC in particular and with respect to the construction industry in general. The results indicated that SHC was doing well in their business performance, and was potential projects often overlap with each other.